The Age of Affirmation - Gasparri, Stefano; Gelichi, Sauro (Brepols, 2018)
This volume brings together the Proceedings of the seminar held on 29 and 30 October 2015 at the Department of Humanities of Ca’ Foscari University of Venice. The title of the book, which is the same as the seminar, refers to the “age of consolidation” of Venice, that had been identified by the promoters of the initiative as the 9<span class=